An?lise de desempenho do acesso oportun?stico ao espectro em uma rede de r?dio cognitivo com multicanais e sensoriamento imperfeito - Branislav, Edgar Feijo Couceiro (2016)
Cognitive radio have emerging as promising technology to tackle the problem of spectrum scarcity by opportunistically exploit the underutilized radio spectrum. In the opportunistic spectrum access (OSA), the secondary network senses the spectrum to identify local and instantaneous spectrum opportunities in order to utilize those opportunities in a nonintrusive manner to the primary communications. In this work, a continuous time Markov chain was used to model and evaluate the performance of the opportunistic spectrum access in a multichannel cognitive radio network with imperfect sensing (false alarms and misdetection). The study is made as an extension for the infinite population assumption already presented in the literature in a way that it can be also consider for the finite user population with arrival rate dependent assumption. Furthermore, numerical results are presented for both approaches. In this work, is also presented a study on the cooperative sensing by decision fusion and the different strategies that can be used on the fusion center in order to achieve different goals. Additionally, a comparison between the performance of the opportunistic spectrum access in a cognitive radio network with cooperative sensing by decision fusion and the performance of the opportunistic spectrum access in a cognitive radio network with non-cooperative sensing is made. Numerical results and discussions are presented throughout the entire study.